FENOMENA CHILDFREE DAN IMPLIKASINYA TERHADAP MAQASHID SYARIAH - Hazmi Naufal Rosyad; Muhammad Zainuddin Sunarto (LPPM STAI Muhammadiyah Probolinggo, 2026)
The childfree phenomenon, defined as the deliberate decision not to have children, has emerged as a significant discourse within modern society, particularly in Indonesia, where cultural and religious values emphasize the importance of family and offspring. In Islamic thought, procreation serves not only a biological function but also plays a crucial role in ensuring the continuity of faith, morality, and the civilization of the Muslim community. This study aims to analyze the childfree choice through the lens of maqāṣid al-sharī‘ah, with a specific focus on the principle of ḥifẓ al-nasl (preservation of lineage). This research employs a qualitative-normative method with a descriptive-analytical approach, examining classical Islamic jurisprudence sources and contemporary scholarly works. The findings indicate that the childfree decision may be considered permissible in Islam when justified by valid reasons, such as safeguarding life, protecting mental health, and addressing rational family welfare considerations, provided that such decisions are temporary. However, permanent rejection of procreation without legitimate reasons, particularly when driven by individualistic or hedonistic ideologies, contradicts maqāṣid al-sharī‘ah, especially the principle of ḥifẓ al-nasl, as it undermines generational continuity and the foundational structure of the Muslim family. Therefore, the Islamic perspective emphasizes a balance between individual autonomy and moral–social responsibility in maintaining the sustainability of the ummah.